Exploring learners' motivation and identifying burnout triggers among foundation students - Muhammad, Fadiatul Hasinah; Ahmad Nazri, Nur Asyikin; Sheikh Suhaimi, Siti Nur Yasmin; Ngah, Suhaiza; Saidin, Nurhafizah; Syed Hamid, Sharifah Shatrah; Rahmat, Noor Hanim (Human Resource Management Academic Research Society, 2024)
The association between motivation and burnout among foundation students in Malaysia is a topic of increasing interest to researchers and educators. This study aims to investigate this relationship by examining specific factors influencing it. Employing a quantitative approach, data is collected from foundation students to explore variables such as value, expectancy, and affective components related to motivation, while also assessing burnout through components of exhaustion and disengagement. Analysis of these factors revealed a moderate correlation between motivation and burnout, indicating the necessity for more focused research to deepen our understanding of their relationship, particularly among foundation students in Malaysia. However, these findings provide evidence that burnout occurs among foundation students, even when they strive with higher motivation. This suggests the need for researchers to develop better instruments to further study the causes of burnout among foundation students.